Sorafenib as Adjuvant Therapy Post–Liver Transplant: A Single-center Experience - Hala Hassanain, MD; Ashton A. Connor, MD, PhD; Elizabeth W. Brombosz, PhD; Khush Patel, MD, MS; Ahmed Elaileh, MD; Tamneet Basra, MD; Sudha Kodali, MD, MSPH; David W. Victor, III, MD; Caroline J. Simon, MD; Yee Lee Cheah, MD; Mark J. Hobeika, MD; Constance M. Mobley, MD, PhD; et al. (Transplantation Direct)
Background. Hepatocellular carcinoma (HCC) has a rising incidence and mortality in North America. Liver transplantation (LT) with adjunctive therapies offers excellent outcomes. However, HCC recurrences are associated with high mortality. We investigate whether adjuvant systemic therapy can reduce recurrence, as shown with other malignancies. Methods. Medical records of patients undergoing LT for HCC at a single center between January 2016 and December 2022 were retrospectively reviewed. Patients were stratified into 3 groups: (1) recipients of adjuvant sorafenib, (2) nonrecipients at high recurrence risk, and (3) nonrecipients at low risk by explant pathology features. The outcomes were overall survival (OS) and recurrence-free survival (RFS). Adjuvant sorafenib recipients were also propensity score matched 1:2 to nonadjuvant recipients based on recurrence risk features. Results. During the study period, 273 patients with HCC underwent LT and 16 (5.9%) received adjuvant sorafenib therapy. Adjuvant sorafenib recipients were demographically similar to nonrecipients and, on explant pathology, had greater tumor burden, lymphovascular invasion, and poorer differentiation (all P < 0.001). Adverse events were observed in 12 adjuvant sorafenib recipients (75%). OS was similar among the 3 groups (P = 0.2), and adjuvant sorafenib was not associated with OS in multivariable analysis (hazard ratio, 1.31; 95% confidence interval, 0.45-3.78; P = 0.62). RFS was significantly lower in sorafenib patients (hazard ratio, 6.99; 95% confidence interval, 2.12-23.05; P = 0.001). Following propensity matching, adjuvant sorafenib use was not associated with either OS (P = 0.24) or RFS rates (P = 0.65). Conclusions. In this single-center analysis, adjuvant sorafenib was not associated with OS. Recipients were observed to have shorter RFS, likely due to the increased prevalence of high-risk features, and sorafenib use was associated with high frequencies of adverse events.